Arginine and di-arginine ligands for plasmid DNA purification using negative chromatography - Cardoso, Sara (2020)
The increasing number of applications requiring highly purified plasmid DNA (pDNA) generates a corresponding need for simple, scalable, and cost-effective purification processes. Due to the pDNA large size and complex shape, the use of commercial chromatographic beads often results in poor yields and low binding capacities when operated in a positive mode. An alternative to overcome this limitation is the design of chromatographic ligand-resin systems able to efficiently operate in negative mode, where host impurities (especially low molecular weight RNA) are efficiently captured and separated from the target pDNA. In this work, arginine amino acid and di-arginine peptide (arginine-arginine) were immobilized in agarose resins and evaluated for negative chromatographic purification of pDNA from bacterial cell lysates. The results showed that RNA was preferentially bound to the ligands, interfering with the binding of pDNA. The amount of plasmid processed per column volume by arginine and di-arginine, under negative mode, was substantially larger comparing with the conventional positive mode, resulting in pDNA recoveries up to 99%, with a considerable reduction of host impurities. This study shows that negative mode chromatography using arginine-based ligands poses as an interesting alternative for intermediate and polishing pDNA purification operations, with considerable economic and environmental advantages.